Schema therapy with couples : a practitioner's guide to healing relationships - Simeone-DiFrancesco, Chiara (Wiley-Blackwell, 2015)
"Schema Therapy for Couples represents the first practitioner guide to detail effective Schema Therapy techniques in couple and relationship therapy. Shows how the distinctive features of ST make it ideal for addressing the cognitive and emotion-focused problems typical in couple relationships Presents and integrates a series of innovative tools and interventions such as Schema Therapy with Needs versus Wants, Mode Cycle Clash Cards, limited re-parenting visualization, and chair work Authored by an international team of experts in couples therapy and Schema Therapy "--